Implementasi pendidikan karakter pada lingkungan dan teknologi - Qomariyah, Rif’atul (Maliki Interdisciplinary Journal, 2024)
The environment and technology are something that is very influential in the formation of the character of education. The use of technology and adaptation to the environment that is quite good and appropriate can be a supporter of the implementation of character education that has become the noble ideals of national education in Indonesia. positive or negative, depending on how individuals use their awareness. In the implementation of character education, to face the increasingly modern technological development, we must know some of the criteria and values ​​that must be instilled and know the process of applying characters supported by agara technology can encourage students to become great in utilizing the teaching appropriately. Character education is an effort to develop themselves from positive values ​​and attitudes in students. There is also the negative impact of technology on student character behavior if it does not use this technology well on character behavior. In an increasingly sophisticated era of technology, the environment and technology play an important role in improving the quality of character education. Therefore this research aims to find out how the implementation of character education in the environment and technology can improve the quality of a student. Character education aims to develop good attitudes ,behavior and thought patterns.